The Stylistic Resources of Occasional Phraseological Units in Rimvydas Valatka’s Comments on Russia’s War in Ukraine - Aleksaitė, Agnė (Verbum, 2024)
The subject of this study is the 201 occasional phraseological units that appear in the comments by the journalist R. Valatka on the Russia–Ukraine war published on the delfi.lt news portal in 2022–2023, said comments totalling 82. The goal of the article is to analyse the structure of the occasional phraseological units and the patterns of their usage. Once the data of the study had been summarised, the following conclusions were made: (1) the texts by this journalist are dominated by two types of modification of phraseological units: the development of a phraseological unit makeup (78; 68.4%) and replacement of phraseological unit components (23; 20.2%); (2) there are three secondary types of reconstruction of phraseological units that are employed: the expansion of a phraseological unit into a broader context (6; 5.3%), several types of modification (5; 4.4%), and using a phraseological unit as a semantic parallelism (2; 1.7%); (3) no other types of modification, such as phraseological unit repetition, variation of phraseological unit value, omission of phraseological unit components, and phraseological unit inversion have been discovered over the period of the study. Modified (114; 56.7%) and author’s own, bespoke (87; 43.3%) phraseological compounds are used for their expression, which is both novel and stronger, as well as the need to highlight the negative emotional charge of the unit.
Keywords: occasional phraseological units; types of modification; opinion journalism; comments; stylistics; war